Peculiarities of mining and technical conditions for construction and operation of Kuznetskovskiy tunnel on the far eastern railway - Kvashuk Sergey; Smyshlyaev Boris; Trunev Vasiliy (MATEC Web of Conferences, 2019)
Kuznetsovskiy tunnel is built in the pass section of Sikhote-Alin Ridge on the Pivan-Sovetskaya Gavan leg of the Far Eastern Railway route, Russia. The tunnel axis is crossed by a system of faults of various capacities. The fault zones are associated with increased fracturing, reduced stability, abundant water inflows in some places, the threat of dumping, intense silicification and sulfide mineralization. The monitoring data obtained by natural pulsed electromagnetic field of the Earth (NPEFE) and dipole electromagnetic proliferation (DEMP) methods made it possible to come to a conclusion about the real picture of the development and to make forecast of the rock pressure, as well as the dynamics of groundwater entering to the workings for the further tunnel's safe construction and operation.